INTEGRASI PENDIDIKAN HOLISTIK-ISLAMI DALAM PENGUATAN SEKOLAH RAMAH ANAK: Studi Kasus di SDIT Arafah Sampit - Khairil Anwar; Gita Anggraini; M. Andi Setiawan (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The implementation of Child-Friendly Schools (CFS) in Islamic elementary schools has focused more on child protection and school policies, while the integration of holistic education with Islamic values ​​remains relatively limited. This study aims to analyze the integration of Holistic-Islamic Education in strengthening Child-Friendly Schools at SDIT Arafah Sampit and to formulate a conceptual model of integration based on empirical findings. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation studies involving the principal, teachers, students, parents, and education personnel. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through data condensation, data presentation, and drawing conclusions. The results show that the integration of Holistic-Islamic Education is realized through six interrelated dimensions: spiritual, intellectual, emotional, social, physical, and aesthetic, which are internalized in school culture, learning processes, and character development. These six dimensions strengthen the implementation of the principles of Child-Friendly Schools by creating a safe, inclusive, participatory, and caring learning environment. These findings demonstrate that the integration of Islamic values ​​with holistic education can form a more comprehensive educational framework for strengthening Child-Friendly Schools. This research produces the Holistic Islamic–Child-Friendly School (HI-CFS) Model as a conceptual contribution that can serve as a reference for Islamic elementary schools in developing a sustainable child-friendly school culture.